The Influence of Digital Financial Literacy and Trust on Fintech Lending Among Gen Z in Malang City - Moch Nurhidayat; Warter Agustim; Fransiska Susanti (International Research and Development for Human Beings (IRDH), 2026)
The purpose of this study was to determine the effect of digital financial literacy and trust on the use of fintech lending among Generation Z in Malang City, both partially and simultaneously. This study employed a quantitative research method. The sample was determined using a purposive sampling technique, resulting in 100 respondents. Data were collected through questionnaires. The data analysis method used was multiple linear regression with the assistance of SPSS version 26. The results showed that partially, digital financial literacy had a significant effect on the use of fintech lending with a t-value of 5.769 and a significance value of 0.001, and trust also had a significant effect on the use of fintech lending with a t-value of 4.310 and a significance value of 0.001. Simultaneously, digital financial literacy and trust had a significant effect on the use of fintech lending with an F-value of 127.088, which was greater than the F-table value of 3.097 and a significance value of 0.001. The results indicate that the higher the level of digital financial literacy and trust, the higher the tendency of Generation Z to use fintech lending services.